Tandem Oxidative Reaction of 1,3-Diarylpropenes and 5-Aminopyrazoles - Cheng, Dongping; Gu, Huafang; Xia, Hongshuang; Wang, Yawei; Li, Jing-Hua; Xu, Xiaoliang (Synlett, 2023)
The reaction of 5-aminopyrazoles with 1,3-diarylpropenes mediated by 2,3-dichloro-5,6-dicyano-1,4-benzoquinone, with subsequent intramolecular cyclization and dehydroaromatization in the presence of Cu(OTf)2/tert-butyl hydroperoxide, gave a series of pyrazolo[3,4-b]pyridines in moderate to excellent yields. The reaction has the advantages of high atom economy, a wide substrate scope, and a one-pot procedure.
Keywords: oxidative coupling; tandem reaction; one-pot reaction; aminopyrazoles; diarylpropenes; pyrazolopyridines